Analysis of PROMETHEE II Method on Selection of Lecturer Community Service Grant Proposals. (August 2019) - Ningsih, Sri Rahayu; Wulansari, Riyani; Hartama, Dedy; Windarto, Agus Perdana; Wanto, Anjar
Abstract: This study aims to determine the recipient lecturers of the service to the internal community at STIKOM Tunas Bangsa. The data were obtained from the archive of the Institute for Research and Service to the Tunas Bangsa STIKOM Community in 2017 and conducted interviews with the Chairperson of the Institute. The alternatives used are 6, namely Situation Analysis (C1), Partner prioritization problems and solutions offered (C2), output targets (C3), accuracy of approach methods to overcome problems, activity plans, partner participation contributions (C4), college feasibility (C5), the cost of work for the feasibility of the proposed cost (C6). The method used in the research of the PROMETHEE II Method. From the results of the study obtained 5 alternatives selected lecturers who received internal service grants, namely: A1 (Net flow 13.79), A5 (Net flow 7.23), A2 (Net flow 7.16), A6 (Net flow 6.29), A3 (Net flow 2.08) of 9 Alternatives. The implementation of the PROMETHEE II method is expected to provide an objective assessment and to compare the results of the reviewer's assessment in determining the recipients of internal service grants. So that it is expected that the decisions given can maintain the quality and quality of the assessment.